DESAIN DAN IMPLEMENTASI PROTOKOL HANDOFF DAN ERROR CHECKING PADA JARINGAN MWSN (MOBILE WIRELESS SENSOR NETWORKS) - Herlambang, Septian Adi; Jusak, Jusak (Journal of Control and Network Systems, 2015)
Over the last decade, the development of WSN (Wireless Sensor Networks)Â  communication technologies so rapidly seen, from some of the concepts that are built using WSN such, an early warning system against floods, temperature and humidity monitoring system on crop land distance. WSN is a wireless network infrastructure that uses a wired or wireless sensors to monitor physical or environmental conditions that may be connected to the network, this network uses radio waves as a medium of delivery.In general, the application of WSN using a static model, but in certain circumstances the static model is not suitable to be applied as the environmental conditions change. Static models may experience problems such as, not all areas can be monitored, some WSN applications that require sensors with a high price quite troublesome.In this MWSN systems we implement a handoff protocol. Handoff or Hand Over (HO) in the process of changing service / lawyers handle a Mobile Station (MS) from a Base Station (BS) to another BS MSÂ  due to the movement from BS to the other BSBased on test results, obtained percentage of data loss (missing data) to the mobile speed by 70% - 80% and the percentage of data loss (missing data) to the distance (in the room) by 30% - 80% while (outdoors) at 50 % - 80%. Based on the test results showed that the distance between the XBee parameters greatly affected the amount of data received, while the parameters of the speed is not too affected.